Improving Pronunciation through the Use of Karaoke in an Adult English Class - Andrés Roberto Rengifo (Universidad Nacional de Colombia, 2009)
Students often have difficulty and experience lots of problems with pronunciation in English. This article is based on a research project which intended to show how students can improve their pronunciation through the use of karaoke in their English class. By using karaoke, the teacher designs activities and involves students to improve their pronunciation. Students' progress is analyzed in order to arrive at a conclusion of the effectiveness of the karaoke sessions. It is also shown that the karaoke classes offer a lot of fun and creativity while students cooperate with each other to achieve their pronunciation goals.